Real‐world outcomes of unrestricted direct‐acting antiviral treatment for hepatitis C in Australia: The South Australian statewide experience. Issue 11 (10th July 2018) - Haridy, J.; Wigg, A.; Muller, K.; Ramachandran, J.; Tilley, E.; Waddell, V.; Gordon, D.; Shaw, D.; Huynh, D.; Stewart, J.; Nelson, R.; Warner, M.; et al.
Summary: In March 2016, the Australian government offered unrestricted access to direct‐acting antiviral (DAA) therapy for chronic hepatitis C virus (HCV) to the entire population. This included prescription by any medical practitioner in consultation with specialists until sufficient experience was attained. We sought to determine the outcomes and experience over the first twelve months for the entire state of South Australia. We performed a prospective, observational study following outcomes of all treatments associated with the state's four main tertiary centres. A total of 1909 subjects initiating DAA therapy were included, representing an estimated 90% of all treatments in the state. Overall, SVR12 was 80.4% in all subjects intended for treatment and 95.7% in those completing treatment and follow‐up. 14.2% were lost to follow‐up (LTFU) and did not complete SVR12 testing. LTFU was independently associated with community treatment via remote consultation (OR 1.50, 95% CI 1.04‐2.18, P = .03), prison‐based treatment (OR 2.02, 95% CI 1.08‐3.79, P = .03) and younger age (OR 0.98, 95% CI 0.97‐0.99, P = .05). Of the 1534 subjects completing treatment and follow‐up, decreased likelihood of SVR12 was associated with genotype 2 (OR 0.23, 95% CI 0.07‐0.74, P = .01) and genotype 3 (OR 0.23, 95% CI 0.12‐0.43, P ≤ .01). A significant decrease in treatment initiation was observed over the twelve‐month period in conjunction with a shift from hospital to community‐based treatment. Our findings support the high responses observed in clinical trials; however, a significant gap exists in SVR12 in our real‐world cohort due to LTFU. A declining treatment initiation rate and shift to community‐based treatment highlight the need to explore additional strategies to identify, treat and follow‐up remaining patients in order to achieve elimination targets.